Effects of Coriolis force on the nonlinear interactions of acoustic-gravity waves in the atmosphere. (1st October 2021) - Chatterjee, Debjani; Misra, A.P.
Abstract: The nonlinear theory of acoustic-gravity waves (AGWs) in the atmosphere is revisited with the effects of the Coriolis force. Previous theory in the literature (Mendonça and Stenflo, 2015) is advanced. Starting from a set of fluid equations modified by the Coriolis force, a general linear dispersion relation is derived which manifests the coupling of the high-frequency acoustic-gravity waves (AGWs) and the low-frequency internal gravity waves (IGWs). The frequency of IGWs is enhanced by the Earth's angular velocity. The latter also significantly modifies the nonlinear coupling of AGWs and IGWs whose evolutions are described by the Zakharov approach as well as the Wigner–Moyal formalism. The consequences of AGWs and the two equivalent evolution equations modified by the Coriolis force are briefly discussed. Highlights: The Coriolis force modifies the propagation of acoustic-gravity waves (AGWs). Nonlinear couplings of AGWs are described by the Zakharov and Wave-kinetic equations. The ponderomotive nonlinearity is enhanced and the resonance condition is modified. The Zakharov approach is udeful for the description of atmospheric solitons. The wave-kinetic approach is useful for the description of atmospheric turbulence.